FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN STUNTING DI KECAMATAN KUALUH SELATAN KABUPATEN LABUHANBATU UTARA TAHUN 2024 - Dalimunthe, Nuraisyah (Akupun Tour Publisher, 2024)
Background: Stunting is defined as height-for-age below-2 standard deviations of the median child growth curve, caused by chronic malnutrition during the first 1,000 days of life. Indonesia is one of the developing countries with a high prevalence of stunting among children under five. According to the Indonesian Nutritional Status Survey (SSGI), North Labuhanbatu Regency has a stunting rate of 7.3%, and the local government is aiming for zero stunting by 2025 (Pemkab Labuhanbatu Utara, 2024). This makes is crucial to implement measures to reduce stunting rates. Purpose: This study aims to identify the factors related to stunting prevention behaviors. Method: The research employs a quantitative method with a cross-sectional design conducted in Kualuh Selatan District, North Labuhanbatu Regency, from January to August 2024. The Population consists of mothers with children under five (0-5 years old) residing in the working area of Simangalam Health Center, totaling 823 individuals. A sample of 89 mothers was selected. Results: The results show a relantionship between knowledge, income level, and support from healthcare workes with stunting prevention behaviors. However, maternal employment was not related to stunting prevention behaviors among mothers with children under five in in the Simangalam Health Center area. Disscusion and Conclusion: It is recommended that mothers of young children continually seek information on stunting prevention to mitigate the risk of stunting. Additionally, it is advised that the head of the health center continues to enhance the role of healthcare workes in Simangalam Health Center, Kualuh Selatan, in educating the public about stunting prevention.